EKSISTENSI TRADISI MATTOANA ARAJANG DI DESA BONTO KECAMATAN SINJAI TENGAH KABUPATEN SINJAI (PERSPEKTIF BUDAYA) - Muhammad arif Arif (JURNAL ILMU BUDAYA, 2022)
This paper aims to explain the Mattoana Arajang Tradition in Bonto Village,  Sinjai Tengah District, Sinjai Regency (In a Cultural Perspective), specifically about how the existence of the Mattoana Arajang tradition in Bonto Village, Sinjai Tengah District, Sinjai Regency. It is a qualitative research using historical, anthropological, sociological and religious approaches. Furthermore, data collection using field research (field), with the data collection stage through observation, interviews, and documentation where the author tries to express the object discussed according to the reality that occurs in the community.  Keyword : Tradition, Mattoana Arajang, glorification, Bonto Village